Weak thresholding greedy algorithms in Banach spaces - Dilworth, S.J.; Kutzarova, Denka; Schlumprecht, Th; Wojtaszczyk, P. (Journal of functional analysis, 2012)
We consider weak thresholding greedy algorithms with respect to Markushevich bases in general Banach spaces. We find sufficient conditions for the equivalence of boundedness and convergence of the approximants. We also show that if there is a weak thresholding algorithm for the system which gives the best n-term approximation up to a multiplicative constant, then the system is already “greedy”. Similar results are proved for “almost greedy” and “semi-greedy” systems.